ECONOMIC IMPACT OF SMOKING REGULATIONS PROPOSED BY THE GENERAL SERVICES ADMINISTRATION - TOLLISON,RD/GEORGE MASON UNIV (Tufts Archival Research Center, 2007)
Report on the economic impact of smoking regulations proposed by the General Services Administration (GSA). Analyzes proposed regulations and discusses and quantifies potential impacts of the policy. Questions specifications of the smoking area and the enforcement of the policy. Finds that taxpayers will bear large costs, in part due to productivity losses. Accuses policy of disciminating against low income people and minorities.